Effect of Magnetized Water and Seeds on the Growth and Yield of Sesame (Sesamum indicum L.) under Irrigation (University of Khartoum Journal of Agricultural Sciences, 2023)
Magnetic treatment is hypothesized to result in theimprovement of the performance of some crops. A field study wasconducted to evaluate the effect of magnetized water and seeds on growthand yield of sesame (cv. Promo). An experiment was carried out for twoconsecutive seasons (2004/05 and 2005/06) in the Demonstration Farm,Faculty of Agriculture, Shambat, Sudan. The seeds were either sowndirectly or after passing them through a magnetic field. The crop receivedequal quantities of either normal or magnetized water every 14 days. Theresults showed that magnetized water and seeds consistently had non-significant positive effect on mean plant height, number of leaves perplant and stem diameter. The plants irrigated with magnetized water tooksignificantly fewer days to flower than their respective untreated plants.Magnetized water and seeds significantly increased seed yield due toincreased number of capsules per plant. In contrast, all treatments had nosignificant effect on mean 1000-seed weight and oil content of seeds.
Keywords: Sesame; magnetic field; irrigation; Sudan